Composite contiguous pile wall and deep mixing column wall as a dam –Design, construction and performance - Supasit Pongsivasathit (Elsevier, 2021)
This paper presents a case study on the application of a composite contiguous-pile wall and deep mixing (DM) column wall as a dam to develop a luxury lake in Lake Legend Chaengwatthana project, Bangkok, Thailand. This dam was constructed in a deep rainwater pond without providing the water removal, which could save on both time and cost construction. The design and construction method were challenging because the dam was located on the soft and thick Bangkok clay. The dam was designed by finite element analyses (FEA) using PLAXIS software. The 2 rows of contiguous-pile walls were first executed and then filled with soft clay. The DM columns were used to strengthen the clay backfill. The FEA results at normal and rain-shortage stages confirm the stability of the dam with accepted deformation. With insignificant water seepage over time, the dam acted as the waterproof barrier. The field performance of the dam during construction and at service state over 276 days were recorded and compared with FEA results. The numerical simulation slightly over-predicted the lateral displacement. The difference in the displacement between the measured and simulated data reduced significantly with depth. The rate of consolidation by the numerical simulation results were slightly slower than that by the field measurement. The outcome of this research will be fundamental to develop a design guideline of ground improvement in soft Bangkok clay and other similar soft clay deposits especially in Southeast Asian countries.